Safety of Intravenous Thrombolysis in Chronic Intracranial Hemorrhage: A Five-Year Multicenter Study - Zand, Ramin; Tsivgoulis, Georgios; Sadighi, Alireza; Singh, Mantinderpreet; McCormack, Michael; Shahjouei, Shima; Goyal, Nitin; Noorbakhsh-Sabet, Nariman; Alexandrov, Anne W; Alexandrov, Andrei V (Journal of stroke and cerebrovascular diseases, 2018)
INTRODUCTION: Although the recently updated U.S. alteplase label removed "history of intracranial hemorrhage (ICH)" as a contraindication, there are very limited data on the safety of intravenous thrombolysis (IVT) in acute ischemic stroke (AIS) patients with chronic ICH. We sought to evaluate IVT safety in AIS patients with a history of ICH. METHODS: We analyzed consecutive AIS patients treated with IVT at 3 tertiary stroke centers during a 5-year period. We identified AIS treated with IVT with clinical history and neuroimaging confirmation of prior ICH. The safety measure was symptomatic ICH (sICH) defined according to European Cooperative Acute Stroke Study-III criteria combined with the clinical deterioration of 4 points or higher in the National Institutes of Health Stroke Scale (NIHSS) or death. RESULTS: Of the 1212 AIS patients treated with IVT, 7 (.6%) (mean age 72 ± 11 years, 57% men, median NIHSS: 5 points, interquartile range: 2-8) had a history of ICH (hematoma volume: 1-21 cm3, elapsed time between previous ICH and AIS: 1.5-12 years, 5 located in basal ganglia and 2 in periventricular white matter). Patients with previous ICH did not differ in terms of demographics and admission stroke severity in comparison with the rest. The 2 groups had similar rates of sICH (0% [0/7] versus 3.6%, P = .61) and in-hospital mortality (0% [0/7] versus 6.0%, P = .50). CONCLUSION: Our study indicates that IVT might be safe among AIS patients with a history of chronic ICH. Further research with a larger sample size is required to confirm our finding and define the shortest time interval between the hemorrhagic and ischemic events that can be associated with the safe administration of IVT.
Keywords: trombolytická terapie; fibrinolytika; výsledek terapie; Disability Evaluation; Řecko; Infusions, Intravenous; hodnocení rizik; Male; retrospektivní studie; intravenózní infuze; Middle Aged; Risk Assessment; Risk Factors; magnetická rezonanční tomografie; mortalita v nemocnicích; posuzování pracovní neschopnosti; Fibrinolytic Agents; Clinical Decision-Making; chronická nemoc; cévní mozková příhoda; Stroke; Aged; mužské pohlaví; senioři; Tertiary Care Centers; ischemie mozku; Chronic Disease; Thrombolytic Therapy; Hospital Mortality; Treatment Outcome; Time Factors; Contraindications, Drug; bezpečnost pacientů; senioři nad 80 let; léková kontraindikace; centra terciární péče; lidé; Greece; United States; ženské pohlaví; Humans; intrakraniální krvácení; časové faktory; rizikové faktory; Aged, 80 and over; Intracranial Hemorrhages; Spojené státy americké; Retrospective Studies; Magnetic Resonance Imaging; klinické rozhodování; Female; Patient Safety; lidé středního věku; Brain Ischemia